2015
DOI: 10.1371/journal.pone.0138272
|View full text |Cite
|
Sign up to set email alerts
|

The Unrecognized Burden of Influenza in Young Kenyan Children, 2008-2012

Abstract: Influenza-associated disease burden among children in tropical sub-Saharan Africa is not well established, particularly outside of the 2009 pandemic period. We estimated the burden of influenza in children aged 0–4 years through population-based surveillance for influenza-like illness (ILI) and acute lower respiratory tract illness (ALRI). Household members meeting ILI or ALRI case definitions were referred to health facilities for evaluation and collection of nasopharyngeal and oropharyngeal swabs for influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…These findings are in contrast to the USA, where rates of influenza‐associated hospitalization are higher in the 0–5‐month age group than in the 6–23‐month age group; however, these differences could reflect an increased likelihood of newborn hospitalizations in the USA for potential sepsis workup investigations. Few studies in Kenya have attempted to describe the incidence of hospitalized influenza‐associated SARI among very young children, yet these findings have an important bearing on the implementation of influenza vaccine policies. While children 6‐23 months of age can be directly vaccinated against influenza, it is recommended that protection of children <6 months of age be provided through maternal vaccination…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in contrast to the USA, where rates of influenza‐associated hospitalization are higher in the 0–5‐month age group than in the 6–23‐month age group; however, these differences could reflect an increased likelihood of newborn hospitalizations in the USA for potential sepsis workup investigations. Few studies in Kenya have attempted to describe the incidence of hospitalized influenza‐associated SARI among very young children, yet these findings have an important bearing on the implementation of influenza vaccine policies. While children 6‐23 months of age can be directly vaccinated against influenza, it is recommended that protection of children <6 months of age be provided through maternal vaccination…”
Section: Discussionmentioning
confidence: 99%
“… 41 The highest estimate from non-US based studies from the 2009 pandemic H1N1 influenza time period was 259 per 10 000 person-years (95% CI 97.0 to 689) in Kenya. 36 …”
Section: Resultsmentioning
confidence: 99%
“…In particular, estimates of rates for LCI hospitalisations, the most frequently reported and best-described outcome among these studies, ranged 10-fold, from 9.3 to 91.2 per 10 000 infants, within the USA alone, and varied even more widely in other settings. The incidence of LCI hospitalisations was generally higher during the 2009 pandemic H1N1 time period (20 per 10 000 infants 40 to 259 36 per 10 000 person-years) than during seasonal influenza years, though few estimates from the H1N1 pandemic time period were available. Our work also highlights the relative lack of studies that specifically report influenza outcomes in this vulnerable age group and the limited information included in studies that do include such findings.…”
Section: Discussionmentioning
confidence: 99%
“…These data have confirmed that influenza is a major cause of hospitalization and severe acute respiratory disease in all settings, whether rich or poor, tropical or temperate, urban or rural ( 17 19 ), and that the risk for severe influenza outcomes might be higher in LMICs than in high-income countries ( 20 ). In South Africa, for instance, rates of influenza-associated mortality among the elderly were 3–4 times higher than those among the elderly in the United States ( 21 ).…”
Section: Progress But Gaps Remainmentioning
confidence: 56%